(untitled) (Journal of actual problems of jurisprudence, 2019)
Article discussed the ways and rules of law, оne of the important trends in the organization of a full and impartial mechanism for charging, the development of a uniform methodology for calculating the specific amount of environmental payment. One of the important trends in the organization of a full and impartial mechanism for charging, the development of a uniform methodology for calculating the specific amount of environmental payment